3-T high-b-value diffusion-weighted MR imaging of hyperacute ischemic stroke in the vertebrobasilar territory = Imagerie de diffusion en IRM 3T à b élevé dans l’accident ischémique hyperaigu du territoire vertébobasilaire - Lettau, Michael; Laible, Mona (Journal of neuroradiology, 2012)
Background and purpose: Diffusion-weighted imaging (DWI) is the key method for diagnosing acute ischemic stroke. Applied b values in stroke diffusion studies are usually in the range of 800–1500 s/mm2, but progress in magnetic resonance (MR) technology now permits higher b values. However, it is uncertain whether high-b-value DW sequences improve the detection of acute and hyperacute ischemic lesions. The aim of this study is to explore the sensitivity of high b values vs standard b values at 3 T in hyperacute stroke in the vertebrobasilar territory. Material and methods: 3-T DWI was performed in referred patients with a clinical diagnosis of hyperacute (< 6 h from onset) cerebral infarction using conventional MR sequences as well as DW sequences. Examinations included the usual DW sequence (b = 1000 s/mm2) and two high-b-value DW sequences (b = 3000 s/mm2 and b = 5000 s/mm2). Patients with hyperacute stroke in the posterior circulation were included if MR imaging, including the usual DW sequence, was normal or if the diagnosis was uncertain.Results: In all six studied patients, ischemic lesions were better visualized with high-b-value DWI compared with the usual DWI. On increasing the b value, DW images appeared to be noisier while white-matter tracts became progressively hyperintense. Conclusion: At 3 T, high-b-value DW sequences may be helpful for diagnosing hyperacute infarctions in the vertebrobasilar territory, but further studies are needed to confirm this hypothesis.